Mechanism of Overlying Strata Migration and Failure During Underground Mining in the Mountainous Carbonate Areas in Southwestern China - Li, Jun; Li, Bin; Gao, Yang; Cui, Fangpeng; He, Kai; Li, Jiangshan; Li, Haowen (Frontiers in Earth Science, 2022)
In this study, theoretical analysis and numerical simulation methods were used to investigate the mechanical mechanism of the migration failure of the overlying strata and the development characteristics of the water-conducting fractured zone (WCFZ) in the mountainous carbonate areas in southwestern China. Due to the block-shaped rock mass structure characteristics of carbonate rocks, this paper considered the rock mass structure of the overlying strata. For the three-hinged arch structure of the block-shaped rock mass, the theory of damage mechanics was used to deduct the recursive calculation formula for the ultimate subsidence of the three-hinged arch structure of the overlying strata. Then, a method for determining the height of the WCFZ (HWCFZ) in the overlying strata under mining conditions was developed. Numerical simulations were carried out to study the stress field, plastic zone, and displacement field of the overlying strata and the dynamic evolution of the WCFZ during the mining process, and it was revealed that there was a positive feedback effect between them. After the mine was mined, due to the change of the stress field of the overlying strata, the overlying strata were mainly subjected to three types of plastic deformation during the fracturing process: tension, shearing, and tensile-shearing. There was a plastic partitioning phenomenon in the overlying strata. Among them, the tensile-slip failure zone was the most severely damaged. And the boundary of the WCFZ and the bending subsidence zone were determined based on the change characteristics of the displacement field. The HWCFZ obtained from the numerical simulations was consistent with the theoretical calculated value (93 m vs. 92.5 m), validating the reliability and accuracy of the theoretical calculation method. Underground mining activities are active in the mountainous carbonate areas in southwestern China, and there are many landslide disasters due to overlying strata collapse, resulting in serious casualties. Therefore, prediction of HWCFZ and stability analysis of mountain need to be carried out for different mines in order to effectively carry out geological disaster prevention and mitigation research.